SUPPLY CHAIN PARTNERSHIP INSTITUTIONAL ANALYSIS ON BROILER PRODUCTION - Novita, Ita; Rochman, Nur (Universitas Djuanda, 2019)
Livestock sub-sector is an important part of agricultural development which in addition aims to meet the needs of food and nutrition of the wider community in order to improve the quality of human resources, it must also be able to improve the welfare of farmers. In the livestock sub-sector, many partnership models have been developed including partnerships in broiler business. In order to improve the welfare of farmers, especially broiler breeders in Bogor regency, good structuring is needed in an effective and efficient supply chain partnership institution. Thus, it can increase farmers' income, and ensure the sustainability of people's livestock business, especially broiler business. This study aims to: 1) Identify institutional supply chain management of broiler businesses; 2) Analyze the performance of supply chain partnership institutional broiler businesses in Bogor regency, West Java province. Primary data is obtained through observation and in-depth interviews (in-depth interviews, while secondary data is obtained from related institutions and literature. Collected data is processed quantitatively and qualitatively descriptive. The results of the study conclude: (1) Broiler breeders, namely: Farmers Mandiri, and partnership breeders, which are divided into partnerships on the basis of verbal agreements and officially partnered farmers in partnership. Independent breeders are those who manage and finance all production input needs needed during the production process and are free to market their products. Partner farmers are farmers who have been bound by cooperation both verbally and in writing with companies supplying DOC, feed, vaccines and medicines, so that these farmers only prepare pens, labor and livestock equipment, because all the needs of DOC, feed and medicine and vaccines have been provided by companies that partner with a. (2) Forms of cooperation in marketing live chicken and meat, namely breeders selling live chickens to traders / brokers who then market to retailers in conventional markets. Marketing in the form of broiler is aimed at consumers (restaurants / restaurants. Independent farmers generally market products through traders), independent farmers are free to market to any collector, while farmers in partnership are obliged to market their products to the core. get higher profits compared to breeders partnering verbally and independently.